Immune disruptions and night shift work in hospital healthcare professionals: The intricate effects of social jet-lag and sleep debt - Faraut, Brice; Cordina-Duverger, Emilie; Aristizabal, Guillen; Drogou, Catherine; Gauriau, Caroline; Sauvet, Fabien; Lévi, Francis; Léger, Damien; Guénel, Pascal (Frontiers in Immunology, 2022)
Objectives: We aimed to examine the effects of circadian and sleep rhythm disruptions on immune biomarkers among hospital healthcare professionals working night shifts and rotating day shifts. Methods: Hospital nurses working either as permanent night shifters (n=95) or as rotating morning (n=39) and afternoon (n=57) shifters kept a daily diary for an entire week on sleep and work schedules. Blood samples were collected at the beginning and end of the last shift during the week, and participants were classified into three groups according to the time of blood sampling: morning (7:00 and 14:00), afternoon (14:00 and 21:00) and night (21:00 and 7:00) shifts. Circulating blood counts in immune cells, interleukin-6 and C-reactive protein concentrationsas well as total sleep time/24 h during work days (TST24w) and free days (TST24f), sleep debt (TSTf-TSTw) and social jet-lag (a behavioral proxy of circadian misalignment) were assessed. Results: Compared with day shifters, night shifters had the lowest sleep duration (TST24w=5.4±1.4h), the highest sleep debt (3.2±1.4 h) and social jet-lag (6.7±2.4 h). Variations of immune biomarkers concentrations were consistent with the expected diurnal variations during day shifts (i.e., lower morning levels , increase during the day, peak value in the evening). By contrast in night shifters, blood concentrations of total lymphocytes, T-helper cells, cytotoxic T-cells, memory B-cells and interleukin-6 levels displayed higher values at 07:00, and lower ones at 21:00 for cytotoxic T-cells, interleukin-6 and neutrophil (but higher values for Natural-Killer cells) as compared to day shifters. Multivariate analyses ruled out significant impact of TST24w, sleep debt, and social jet-lag on immune biomarkers concentrations among day shifters. In contrast, among night shifters, multivariate analyses indicated a combined effect of total sleep time (TST24w), sleep debt and social jet-lag for total lymphocytes and T-helper cells but only a social jet-lag effect for interleukin-6 and a single total sleep time effect for neutrophil and B-Cells. Conclusions: Altogether, our results point to intricate response patterns of immune rhythms to circadian misalignment and sleep debt in night shifters. Specifically, these altered pattern expressions of immune cells may increase vulnerability to infections and reduce vaccination efficiency in night workers.